Social contagion of ethnic hostility - Bauer, Michal; Cahlíková, Jana; Chytilová, Julie; Želinský, Tomáš (Proceedings of the National Academy of Sciences - PNAS, 2018)
Interethnic conflicts often escalate rapidly. Why does the behavior of masses easily change from cooperation to aggression? This paper provides an experimental test of whether ethnic hostility is contagious. Using incentivized tasks, we measured willingness to sacrifice one’s own resources to harm others among adolescents from a region with a history of animosities toward the Roma people, the largest ethnic minority in Europe. To identify the influence of peers, subjects made choices after observing either destructive or peaceful behavior of peers in the same task. We found that susceptibility to follow destructive behavior more than doubled when harm was targeted against Roma rather than against coethnics. When peers were peaceful, subjects did not discriminate. We observed very similar patterns in a norms-elicitation experiment: destructive behavior toward Roma was not generally rated as more socially appropriate than when directed at coethnics, but the ratings were more sensitive to social contexts. The findings may illuminate why ethnic hostilities can spread quickly, even in societies with few visible signs of interethnic hatred.